Peer Teaching as a Strategy for Developing Teaching Competence among Office Administration Students - Andi Rizka Ekaputri; Rudi Salam (PINISI Discretion Review, 2026)
The development of teaching competence among Office Administration students is essential because prospective educators must be able to transform theoretical knowledge into effective, confident, and reflective teaching practice. This study aims to analyze peer teaching as a practice-based learning strategy for developing teaching competence among Office Administration students. The study was conducted in the Office Administration Education Study Program at Universitas Negeri Makassar, Indonesia, using a descriptive quantitative research design. The participants consisted of 11 undergraduate students who were involved in peer teaching activities as part of the learning process. Data were collected through structured performance assessment based on several components, including participation, teaching device preparation, first teaching performance, second teaching performance, and final mastery. The findings show that peer teaching provides a meaningful learning experience that enables students to strengthen their participation, prepare teaching devices, practice instructional delivery, communicate learning materials, and build confidence in teaching situations. The overall mastery score indicates that students’ teaching competence was generally in the good to excellent category. The highest achievement was found in the participation and teaching device aspects, while the first teaching performance aspect showed the lowest score, indicating the need for more intensive guidance in confidence, classroom opening skills, communication clarity, classroom management, and nervousness control. These findings suggest that peer teaching is not merely an assessment activity but also a reflective learning process that supports students’ pedagogical readiness through direct practice, feedback, observation, and improvement. This study contributes to teacher education literature by emphasizing the relevance of peer teaching in developing teaching competence within Office Administration education.